Community structure and diversity of myxobacteria in soils from Inner Mongolia, China - Wu, Zhihua; Li, Songyuan; Wang, Xuehan; Liu, Huirong (Frontiers in Microbiology, 2025)
Myxobacteria are a special kind of Gram-negative bacteria that can slide and produce a variety of bioactive substances against bacteria, fungi, and viruses. It has great development and research value in medicine and agriculture. Although myxobacteria have become a research hotspot at home and abroad, there are few systematic studies on the relationship between its diversity, geographical location, and environment factors. In order to solve these problems, 133 soil samples were collected from the east to the west of Inner Mongolia Autonomous Region and divided into five groups. The water content, pH, organic matter, available phosphorus, hydrolytic nitrogen, and available potassium content of soil samples were determined by national standards and other methods. The quantitative assessment of the abundance of myxobacteria in the soil sample was performed by quantitative real-time PCR. The composition of myxobacteria in the soil was determined by 16S rRNA high-throughput sequencing technology to analyze the differences in the community structure of myxobacteria among different groups, explore the relationship between the diversity of myxobacteria resources and the distribution and physical and chemical properties of the soil, and predict and analyze its community function. The results showed that there were abundant myxobacteria resources in the soils of Inner Mongolia, and the average relative abundance of myxobacteria in the soil samples from the central part of Inner Mongolia was higher than that in the eastern and western parts, but the richness and diversity of samples from the central to eastern regions were significantly higher than those from the western regions. The myxobacteria resources in the whole region included 10 families and 22 genera, among which the dominant genera were Labilitrix, Sandaracinus, Archangium, and Haliangium. The analysis of the species composition of myxobacteria among different groups found that the distribution of soil and soil type had an impact on the species composition of the samples. The species with significant differences in relative abundance among the five groups of samples were Labilitrix, Archangium, Sandaracinus, Minicystis, Polyangium, and Myxococcus. In addition, the latitude and longitude of the sampling point and the soil pH, water content, available phosphorus content and organic matter content had a greater impact on the myxobacteria community structure of samples, while the altitude of the soil sample and the contents of available potassium and alkaline nitrogen had a relatively small impact. Our data suggest that the distribution, type and nutrient composition of soil samples have an impact on the relative abundance and species composition of myxobacteria community. The completion of this work can provide basic data for the in-depth study of myxobacteria in the soil.